Numerical assessment of fatigue design curve of welded T-joint improved by high-frequency mechanical impact (HFMI) treatment. (December 2017) - Deng, Caiyan; Niu, Yaru; Gong, Baoming; Liu, Yong; Wang, Dongpo
Highlights: The fatigue performances of HFMI treated welded joints were numerically investigated by structural hot spot approaches. Through thickness at the weld toe approach can effectively study the thickness effect for HFMI treated joints. The thickness correction exponents for HFMI treated T-joints increase with material strength, whilst a reverse thickness effect is observed. The S–N slope m varying with yield strength is more proper for HFMI improvement assessment. Abstract: In the paper, the fatigue performances of as-welded T-joint and T-joint improved by high frequency mechanical impact (HFMI) were numerically investigated using structural hot spot stress approaches: linear surface extrapolation (LSE) and through thickness at the weld toe (TTWT). The effects of main plate thickness and material strength for HFMI-treated joints were investigated. The results showed that the TTWT method was more effective to study the effect of thickness on T-joints improved by HFMI treatment than LSE method. For as-welded T-joints, the thickness correction exponent n  = 0.04 was obtained when the attachment plate thickness was set as constant. For HFMI-treated T-joints, a reverse thickness effect was observed with negative thickness correction exponents, and the thickness correction exponents increased with material strength. In addition, the adoption of S–N slope varying with yield strength was proven to be more proper for HFMI improvement assessment.